Аналітичне обґрунтування кінематичних параметрів копача коренеплодів та цибулевих культур - Теслюк, Геннадій Володимирович; Тeslyuk, Genadiy; Волик, Борис Анатолійович; Volyk, Borys; Когут, І. М.; Kogut, I. (Дніпровський державний аграрно-економічний університет, 2014)
• Запропоновано нову конструкцію віброкопача столових коренеплодів та цибулевих культур, побудованого на принципах об’ємної дії замкнених вібруючих стояків. Підкопування відбувається безконтактним способом, тобто в процесі роботи поверхні копача не стикаються з об’єктом підкопування. Проаналізовано кінематику робочого органа та визначено раціональні параметри кінематичного режиму для різних варіантів підкопування. It is proposed a new design of root vegetables and bulbous crops vibratory digger, built on the principles of closed vibrating poles volumetric action. A distinctive feature is that digging occurs by contactless method, it means that digger working parts do not contact with the digging object during the working process. This helps to minimize crops damage, which is one of the basic conditions for their storage.Field studies showed the dependence between the quality of digging and the degree and uniformly of soil crumbling. It was confirmed the hypothesis, that the roots digging out is most intense, if more than 50 % aggregates formed by the crumbling soil are smaller than roots.The article analyzes the kinematics of working organ and defines the rational parameters of kinematic regime in various digging versions: with soil throwing away along the cutting line, with throwing away vertically up and in the direction of getting away from the working surface of the ploughshare.
Analytical study of root and bulbous crops digger kinematic parameters
Keywords: столові коренеплоди; roots; цибулеві культури; bulbous crops; віброкопач безконтактної дії; contactless vibrating digger